Initial returns of Shariah versus Non-Shariah IPOs: are there any differences? - Ruzita Abdul-Rahim,; Nor Azizan Che-Embi, (Penerbit Universiti Kebangsaan Malaysia, 2013)
This study examines a sample of 384 initial public offerings (IPOs) issued and listed on Bursa Malaysia from January 1999 to December 2008. The objectives of this study are to examine the difference in initial returns of Shariah versus non-Shariah IPOs and the factors that explain the initial returns of these IPOs. A matched sample of Shariah IPOs, which contains the same number of IPOs and share similar characteristics with the non-Shariah IPOs, is created to ensure a more compatible comparison. The results of the difference tests consistently show that the initial returns of non-Shariah IPOs are not statistically different from those of all and matched sample of Shariah IPOs. The cross-sectional multiple regressions yield results demonstrating that Shariah and non-Shariah IPOs share only one common factor: allocation rate. Other than the sole common factor, the initial returns of non-Shariah IPOs are determined by external factors, namely the reputation of the underwriter and the condition of the market. On the contrary, the initial returns of the Shariah IPOs (all) depend on internal factors, namely the size of the offer; the age of the firm; and the ownership of the top five shareholders. As far as the result of the matched Shariah sample is concerned, none of the other variables are significant in explaining the initial returns.